PENINGKATAN KUALITAS GURU DALAM PEMBELAJARAN MATEMATIKA SD MELALUI PENERAPAN REFLECTIVE TEACHING - Debrine Stefany; Yeni Puji Astuti (Universitas PGRI Madiun, 2016)
This study aims to encourage teachers to open up the flow of his thoughts and give an overview for teacher to constantly think very reflective of what has done, doing, and will do in the classroom. The research was conducted three times meeting in SDN Pangarangan I Sumenep , SDN Kolor II Sumenep , and SDN Pandian I Sumenep. The methods used in this study are qualitative and quantitative. The data was obtained as follows : (1) the process of development of teachers in designing lesson plans elementary mathematics is done through a phase of defining, designing, and development; (2) the quality of teachers in developing learning tools is increasing , the quality of teachers in managing learning activities is increasing, and the quality of teachers in materialize learning is increasing while the results of a student's response to learning that has done get good response then obstacles/barriers during the learning process only was found in trials meeting 1 for SDN Kolor II is located on teachers and SDN Pandian I is located on the teachers and students are not found obstacles/barriers during the learning process at SDN Pangarangan I; (3) the results of the application of reflective teaching is considered successful because of increased quality at every meeting held.The results of this research as a scientific contribution in the field of education on improving the quality of Primary teacher in teaching mathematics through the application of reflective teaching that both innovative and easy to apply in teaching.Keywords: Teacher Quality, Reflective Teaching .